Clasificación de las oraciones de relativo: límites, soluciones y nueva propuesta - Álvarez García, Esther (El Colegio de México, 2021)
This paper reviews the principal way in which relative have been classified in the Hispanic world with the purpose of establisshing possible equivalences beetween them. Mention is also made of the principal problems the different proposals present and which are frequently a consequence of including only prototypical examples in any given classification and thereby leaving aside a wide variety of relative constructions. Finally, we propose our own classification of relative clauses with the aim of solving the problems previously presented.